Becoming a Financially Smart Generation: Strategies for Improving Financial Literacy in Senior High Schools in Surakarta City - Rica Nurjanah; Dhany Efita Sari (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to analyze the role of economics teachers in improving students' financial literacy, as well as to identify the challenges, constraints, and strategies implemented by schools. The subjects of the study include grade X social science students, economics teachers, and curriculum staff. The research method used is qualitative with a case study approach, and data collection techniques include structured interviews, observations, and documentation. Data analysis is conducted using the Miles and Huberman interactive model with the aid of NVivo 15 software. The results show that teachers play a significant role in enhancing financial literacy through teaching, motivation, and training. However, challenges faced include limited time, lack of student interest, and the absence of a specific financial literacy curriculum. The school also implements strategies such as cooperation with Bank Danamon, seminars, workshops, and the P5 Entrepreneurship program to support financial literacy. It is recommended that schools strengthen financial literacy programs to produce financially literate students.